APLIKASI ALGORITMA SOLLIN DALAM PENCARIAN POHON PERENTANG MINIMUM PROVINSI JAWA TENGAH - WULAN ANGGRAENI (Faktor Exacta, 2015)
The purpose of this study is to find the minimum range tree of Central Java province by using sollin algorithm. This was research study by using literature study. Tree range minimum is a tree range which has minimum point from a graft. Looking for minimum range tree of Centre Java Province by using algorithm sollin with the solution by using matlab (matrix laboratory). Sollin algorithm is a combination between algorithm prim and kruscal. The way of working was choosing the left side from one point. Every point was identified. After identification process. Next step was checking cutset sides, and the most minimum cutset, so one tree with another tree was connected. After doing the identification by using algorithm sollin so it was got point of minimum tree range was 1251 km. Keywords: graf, minimum spanning tree, algoritma sollin.